KALIMAT TUNGGAL DAN MAJEMUK BAHASA MELAYU DIALEK DALU-DALU KECAMATAN TAMBUSAI - Etri Wermi (Balai Bahasa Provinsi Riau, 2015)
The aim of this research is in order to prevent the fading of Dalu-Dalu Kecamatan Tambusai Dialect of Malay language from other regional languages, so that the original language will not extinguish. This research was handled in the middle of April 2004 until finish, in DaluDalu, Kecamatan Tambusai. The material compositions are the theory used, dialect, syntax meaning, language variation, and single sentences, simple sentences, aquivalent compound sentences. The materials were analyzed by using descriptive method. Data collecting technique without statisticts. After doing the research for approximately three months, it can be concluded that Dalu-Dalu dialect of Malay language is used by communiy in communication formally and informally.